The importance of fungi and of mycology for a global development of the bioeconomy - L. Lange; L. Bech; P.K. Busk; M.N. Grell; Y. Huang; M. Lange; T. Linde; B. Pilgaard; D. Roth; X. Tong (IMA Fungus)
The vision of the European common research programme for 2014–2020, called Horizon 2020, is to create a smarter, more sustainable and more inclusive society. However, this is a global endeavor, which is important for mycologists all over the world because it includes a special role for fungi and fungal products. After ten years of research on industrial scale conversion of biowaste, the conclusion is that the most efficient and gentle way of converting recalcitrant lignocellulosic materials into high value products for industrial purposes, is through the use of fungal enzymes. Moreover, fungi and fungal products are also instrumental in producing fermented foods, to give storage stability and improved health. Climate change will lead to increasingly severe stress on agricultural production and productivity, and here the solution may very well be that fungi will be brought into use as a new generation of agricultural inoculants to provide more robust, more nutrient efficient, and more drought tolerant crop plants. However, much more knowledge is required in order to be able to fully exploit the potentials of fungi, to deliver what is needed and to address the major global challenges through new biological processes, products, and solutions. This knowledge can be obtained by studying the fungal proteome and metabolome; the biology of fungal RNA and epigenetics; protein expression, homologous as well as heterologous; fungal host/substrate relations; physiology, especially of extremophiles; and, not the least, the extent of global fungal biodiversity. We also need much more knowledge and understanding of how fungi degrade biomass in nature.The projects in our group in Aalborg University are examples of the basic and applied research going on to increase the understanding of the biology of the fungal secretome and to discover new enzymes and new molecular/bioinformatics tools.However, we need to put Mycology higher up on global agendas, e.g. by positioning Mycology as a candidate for an OECD Excellency Program. This could pave the way for increased funding of international collaboration, increased global visibility, and higher priority among decision makers all over the world.